Predictors, motives, sources and patterns of nonmedical use of prescription drugs among youths in Buea, Southwest region of Cameroon: A mixed method analysis - Henry Dilonga Meriki; Kukwah Anthony Tufon; Ndohtabi Jerry Eyong; Oru Ivo Ita; Tamanjong Armstrong Ntohyingwe (Emerging Trends in Drugs, Addictions, and Health)
Background: The non-medical use of prescription drugs (NMUPD) is an emerging phenomenon of serious public health concern among young people globally. This study seeks to determine the predictors, motives, sources, patterns of use of NMUPD among youths in the Buea Health District of the South west region. Materials and Methods: A mixed-method community-based, cross-sectional study conducted from May to June 2018, enrolled participants aged 15 - 29 years from schools and community. A pretested semi-structured questionnaire was used to capture data and focus group discussions and key informant interviews were conducted. Quantitative and qualitative analyses were performed with SPSS version 24 and ATLAS.ti version 7 respectively. Logic regression analysis were carried at 5 % significance level. Results: The study enrolled 464 participants (median age of 21 years, IQR: 18 – 23.8 years) into the quantitative study, 63 % were females. Forty-nine participants were enrolled for the qualitative study. A total of 90 (19.6 %; CI: 15.9 – 23.3 %) participants accepted they have used prescriptions medications in the last 12 months for non-medical purposes. Opioids (74.4 %) particularly tramadol (60.1 %) were the most common drugs used. Male gender (p = 0.001), the age group 20–24-year, smoking (p = 0.043) and use of illicit substances (p < 0.001) were independent predictors of NMUPD. Prominent motivations were:- curiosity (31.1 %) and enhancement of work performance (30 %). Unregistered pharmacies and private health facilities were the main sources of these drugs which are acquired mainly without prescription. Conclusion: Male gender, young adults, smoking and use of illicit substances were independent predictors of NMUPD. Motives were hinged to enhancement of performance in various domains of social life. Opioids, particularly tramadol was the predominant drug used, acquired without prescription from unregistered pharmacies. Findings of this study provide baseline evidence that could guide policies on drug prevention, treatment and harm reduction interventions.